Utilizing the mental health nursing workforce: A scoping review of mental health nursing clinical roles and identities - Hurley, John; Lakeman, Richard; Linsley, Paul; Ramsay, Mike; Mckenna‐Lawson, Stephen (International journal of mental health nursing, 2022)
Despite rising international needs for mental health practitioners, the mental health nursing workforce is underutilized. This is in part due to limited understandings of their roles, identities, and capabilities. This paper aimed to collate and synthesize published research on the clinical roles of mental health nurses in order to systematically clarify their professional identity and potential. We searched for eligible studies, published between 2001 and 2021, in five electronic databases. s of retrieved studies were independently screened against exclusion and inclusion criteria (primarily that studies reported on the outcomes associated with mental health nursing roles). Decisions of whether to include studies were through researcher consensus guided by the criteria. The search yielded 324 records, of which 47 were included. Retained papers primarily focused on three themes related to mental health nursing clinical roles and capabilities. Technical roles included those associated with psychotherapy, consumer safety, and diagnosis. Non‐technical roles and capabilities were also described. These included emotional intelligence, advanced communication, and reduction of power differentials. Thirdly, the retained papers reported the generative contexts that influenced clinical roles. These included prolonged proximity with consumers with tensions between therapeutic and custodial roles. The results of this scoping review suggest the mental health nurses (MHNs) have a wide scope of technical skills which they employ in clinical practice. These roles are informed by a distinctive cluster of non‐technical capabilities to promote the well‐being of service users. They are an adaptable and underutilized component of the mental health workforce in a context of escalating unmet needs for expert mental health care.